Adverse events following immunization of co- and separate administration of DTaP-IPV/Hib vaccines: A real-world comparative study - Yiqing Zhu; Li Sun; Yihan Wang; Jinghui Wang; Yafei Wang; Jing Li; Lina Wang; Yu Guo (Taylor & Francis Group, 2024)
To fully understand the safety of DTaP-IPV/Hib vaccination, we evaluated the differences between DTaP-IPV/Hib co-administration and separate administration of the DTaP, IPV and Hib vaccines (DTaP+IPV+Hib) based on adverse events following immunization (AEFI). All AEFI reported in Hebei Province, China, between 2020 and 2022 were included in this study. The risk difference (RD%), relative risk (RR), and Chi-square value were used to compare the differences in reported rates of AEFI between the DTaP-IPV/Hib and DTaP+IPV+Hib groups. From 2020 to 2022, 130 AEFI cases were reported in Hebei Province after DTaP-IPV/Hib vaccination, corresponding to an AEFI reported rate of 66.9/million doses, which was significantly lower than that for DTaP+IPV+Hib (9836 AEFI with a reported rate of 637.8/million doses). The overall reported rate of non-severe AEFI for DTaP+IPV+Hib vaccines was 9.5 times that of DTaP-IPV/Hib vaccination [95% confidence interval (CI): 8.0, 11.3]. Meanwhile, the reported rate of AEFI among infants aged 0-1 y was 9.8 times higher for DTaP+IPV+Hib than for DTaP-IPV/Hib (95% CI: 8.2, 11.7). DTaP+IPV+Hib vaccination also resulted in higher risks of high fever, localized redness and swelling, localized induration, and allergic rash compared with DTaP-IPV/Hib vaccination. The risk of AEFI, which were mostly mild reaction, was higher after vaccination with DTaP+IPV+Hib than after DTaP-IPV/Hib vaccination.